2014
DOI: 10.1371/journal.pone.0089381
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention Measures Predict Pedestrian Detection in Central Field Loss: A Pilot Study

Abstract: PurposeThe ability of visually impaired people to deploy attention effectively to maximize use of their residual vision in dynamic situations is fundamental to safe mobility. We conducted a pilot study to evaluate whether tests of dynamic attention (multiple object tracking; MOT) and static attention (Useful Field of View; UFOV) were predictive of the ability of people with central field loss (CFL) to detect pedestrian hazards in simulated driving.Methods11 people with bilateral CFL (visual acuity 20/30-20/200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Driving is a more complex task, and the attentional mechanisms involved in driving may not be accurately represented when performing the UFOV task. The MOT, which is a more dynamic and sustained assessment of executive control, was proposed and was found to correlate to driving performance ( Alberti, Horowitz, et al, 2014 ; Bowers et al, 2011 ). In this current study, we also found evidence to support the claims that better performance on the MOT predicts better driving performance (see Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Driving is a more complex task, and the attentional mechanisms involved in driving may not be accurately represented when performing the UFOV task. The MOT, which is a more dynamic and sustained assessment of executive control, was proposed and was found to correlate to driving performance ( Alberti, Horowitz, et al, 2014 ; Bowers et al, 2011 ). In this current study, we also found evidence to support the claims that better performance on the MOT predicts better driving performance (see Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those who performed worse on the MOT task also had higher error scores on a road test ( Bowers et al, 2011 ). In addition, MOT was found to be a stronger predictor than UFOV in predicting the ability to detect hazardous pedestrians during simulated driving in those with central visual field loss ( Alberti, Horowitz, Bronstad, & Bowers, 2014 ). These results highlight not only the link between attentional function and driving but also suggest the importance of incorporating a dynamic assessment of sustained visual attention when studying driving performance.…”
Section: Measuring Attentional Function and Its Relation To Driving Pmentioning
confidence: 99%
“…CFL participant RTs were also longer than NV for pedestrians not occluded by the scotoma. Reasons for this may include reduced contrast sensitivity due to increased retinal eccentricity and reduced attentional resources due to the effort required to maintain eccentric fixation with the PRL [ 27 , 28 ]. Our simulator studies provide a specific mechanism by which AMD may cause difficulty in driving and perhaps cessation altogether.…”
Section: Discussionmentioning
confidence: 99%
“…Several patient groups show poor performance on the UFOV test, including those with ophthalmological and neurological diseases (Alberti, Horowitz, Bronstad, & Bowers, 2014;Badenes et al, 2014;Classen et al, 2011;Fisk, Novack, Mennemeier, & Roenker, 2002;Rosen et al, 2015). In addition, UFOV performance declines with increasing age (Ball, Beard, Roenker, Miller, & Griggs, 1988;Edwards et al, 2006;Sekuler, Bennett, & Mamelak, 2000).…”
Section: Introductionmentioning
confidence: 99%